PENINGKATAN PRESTASI BELAJAR BAHASA ARAB ASPEK AT-TARĀKIB DENGAN STRATEGI DRILL BERBASIS ACCELERATED LEARNING - Helmy Fauzi Awaliyah (Muhamadiyah, 2018)
This research is based on the fact that the low Arabic values of the At-Tarākib aspect of the 11th grade students of Accounting Muhammadiyah 2 Yogyakarta. This is due to several factors, including inappropriate learning models and strategies. This research is a classroom action research (CAR) consisting of two cycles. This aims to determine the improvement of learning achievement in Arabic aspects of At-Tarākib. The results showed that learning with the Drill-based Accelerated Learning strategy could improve the achievement of learning Arabic in the aspect of At Tarākib. In first cycle the average value of pre-test score was 48 and post-test score 70, so the increase was 22. The meaning of students' understanding of the material increased. Some students are able to make material concept maps and can make sentences according to the material. In the second cycle the pre-test score was 66 and the post-test score was 84, so the increase was 24. The average post-test increase from the first cycle in the second cycle was 14. Its meaning, most students were able to make concept maps about the material and were able make sentences according to the material.